2018
DOI: 10.3390/met8010034
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio-Based Modelling of the Yield Strength in High-Manganese Steels

Abstract: An ab initio-based model for the strength increase by short-range ordering of C-Mn-Al clusters has been developed. The model is based on ab initio calculations of ordering energies. The impact of clusters on the yield strength of high-manganese austenitic steels (HMnS) is highly dependent on the configurational structure of the cells that carbon atoms will position themselves as interstitial atoms. The impact of the alloying elements C, Mn, and Al on the potential and actual increase in yield strength is analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…When a stress is applied, the planar slip of dislocations destroys the short-range C-Mn clusters as the C atom reorients from the octahedral to the tetrahedral position. The change in the position of the C atom provides temporary disruption of the C-Mn cluster, causing the strength to drop [ 17 , 19 ]. The SRC can be restored by a short-range jump of the C atom from tetrahedral position to nearby octahedral position owing to the low activation energy for reorientation of the C-Mn complex [ 13 , 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a stress is applied, the planar slip of dislocations destroys the short-range C-Mn clusters as the C atom reorients from the octahedral to the tetrahedral position. The change in the position of the C atom provides temporary disruption of the C-Mn cluster, causing the strength to drop [ 17 , 19 ]. The SRC can be restored by a short-range jump of the C atom from tetrahedral position to nearby octahedral position owing to the low activation energy for reorientation of the C-Mn complex [ 13 , 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 40,48 ] The increase in YS is repeatedly attributed to the hindrance of the dislocation movement or a combined effect of ordering and dislocation hindering. [ 49–51 ] We found that the strength increase intensifies with longer aging times and higher pre‐deformation (Figure 2b). A higher pre‐deformation comes along with a higher dislocation density, which as well increases the probability for the displacement of carbon atoms on tetrahedral interstitial sites during straining.…”
Section: Discussionmentioning
confidence: 93%
“…However, all the structures studied with different mutual arrangements of Fe and Cr atoms, according to the B/G criterion [17], refer to plastic materials: B/G=2.25-3.25 (higher than 1.75). Determination of the yield strength of high-manganese steels alloyed with Al on the basis of a model that included the DFT calculations of the contribution of short-range ordering energy was carried out in [18]. In contrast to works [15,16], instead of superlattices, the simulation was performed on the basis of calculating the energy of clusters with an FCC lattice and the octahedral pore filled with carbon in the center.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%